The P2B Regulation and its Effects on Competition and Consumer Choice in Digital Markets in the Perspective of Abuse of Dominance by Ranking - Kyllöinen, Susanna (My University, 2021)
This thesis aims to identify and analyse the challenges and regulatory measures needed in the digital economy. Digitalisation affects on competition and consumer welfare, and it can also affect how consumers live their lives. To reach the aim of the thesis, forming an overall understanding of the digital economy is necessary. Also, learning how platforms and search engines operate on the digital markets and how they may influence the competitive markets, fairness in platform-to-business relationships and most importantly, on consumer choice through search results, is essential. This thesis will examine the Regulation (EU) 2019/1150 of the European Parliament and of the Council of 20 June 2019 on promoting fairness and transparency for business users of online intermediation services (P2B Regulation). The P2B Regulation entered into force due to the digitalisation of the economy, market dominance and expansion of the digital platforms, as well as the need for more fairness and transparency in the digital markets. One of the matters that led to acknowledging the need for the P2B Regulation was the Google Search (Shopping) case. Therefore, this thesis analyses the case in the view of ranking as the ranking biases performed by leading platforms can distort users’ perception of the market. This thesis will systematise the impacts that the P2B Regulation has on the application of competition law and consumer welfare. In this thesis, the purpose is to clarify the governing legal framework by using legal dogmatic approach. This research considers the societal and economic perspectives and uses a method called Law and Technology. The material used for the thesis consists mainly of EU competition law research related to the platform economy. The conclusion of this thesis suggests that the P2B Regulation has helped improve transparency and fairness in the digital markets, which indirectly improves consumer welfare. Also, consumers are more informed about ranking, and, therefore, consumers have gained a better understanding of how the platforms operate. However, the P2B Regulation is complementary, and competition law still holds the position as the primary legislative tool in the digital economy.

Tutkielman tavoitteena on tunnistaa ja analysoida digitaalisen talouden haasteita ja sääntelytoimenpiteitä. Digitalisaatio vaikuttaa kilpailuun ja kuluttajien hyvinvointiin, ja se voi vaikuttaa myös siihen, miten kuluttajat elävät elämäänsä. Tutkielman tavoitteen saavuttamiseksi tarvitaan kokonaisymmärrys digitaalisesta taloudesta. On myös tärkeää oppia, miten alustat ja hakukoneet toimivat digitaalisilla markkinoilla ja miten ne voivat vaikuttaa kilpailukykyisiin markkinoihin, oikeudenmukaisuuteen ja kuluttajavalintaan hakutulosten kautta. Tutkielma tarkastelee 20 päivänä kesäkuuta 2019 voimaan astunutta Euroopan parlamentin ja neuvoston asetusta (EU) 2019/1150 oikeudenmukaisuuden ja avoimuuden edistämisestä verkossa toimivien välityspalvelujen yrityskäyttäjiä varten (P2B-asetus). Asetus säädettiin digitalisoitumisen, digitaalisten alustojen määräävän markkina-aseman lisääntymisen sekä digitaalisten markkinoiden oikeudenmukaisuuden ja avoimuuden tarpeen vuoksi. Yksi niistä asioista, joka johti P2B-asetuksen tarpeen tunnustamiseen, oli Google Search (Shopping) -tapaus. Tutkielmassa siten analysoidaan kyseistä tapausta, varsinkin koska johtavien alustojen rankinglistaukset voivat vääristää kuluttajien käsitystä alustamarkkinoista. Tutkielma systematisoi ja tulkitsee P2B-asetuksen vaikutuksia kilpailulainsäädännön soveltamiseen ja kuluttajien hyvinvointiin. Tutkielman tarkoituksena on selkeyttää oikeudellista kehystä oikeusdogmaattisella lähestymistavalla. Tutkielma tarkastelee myös yhteiskunnallisia näkökulmia ja tutkielmassa käytetään apuna menetelmää nimeltä Law and Technology. Tutkielman lähdemateriaalina on käytetty enimmäkseen EU:n tasoista kilpailuoikeudellista tutkimusta alustataloudesta. Tutkielman johtopäätöksen mukaan P2B-asetus on auttanut parantamaan avoimuutta ja oikeudenmukaisuutta digitaalisilla markkinoilla, mikä parantaa välillisesti kuluttajien hyvinvointia. Kuluttajat ovat myös tietoisempia rankinglistauksista, ja siksi he ovat saaneet paremman käsityksen alustojen toiminnasta. P2B-asetus on kuitenkin luonteeltaan täydentävä, ja kilpailulainsäädäntö on edelleen ensisijainen lainsäädäntöväline digitaalitaloudessa.
Keywords: competition law, consumer behaviour, consumers, digitalisation, EU regulation, Google, platform economy, ranking